2017
DOI: 10.1002/jsfa.8246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent CO2 convection under far‐infrared radiation on vacuum drying of pre‐osmodehydrated watermelon

Abstract: The novel CO convective drying of watermelon in the presence of far-infrared radiation demonstrated an energy-efficient and time-saving operation rendering a dehydrated watermelon with acceptable quality parameters. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The osmotic dehydration is conducted for rinds to produce candies (Hani et al., 2014). However, Chakraborty & Mondal (2017) used osmotic dehydration as a pretreatment to vacuum infrared drying of rectangular slabs. Immersing rinds in sucrose solution for 14 h at 50 °C is the preferred condition for candies with the most acceptable characteristics (Hani et al., 2014).…”
Section: Pre‐processed Fruits and Their Process Conditionsmentioning
confidence: 99%
“…The osmotic dehydration is conducted for rinds to produce candies (Hani et al., 2014). However, Chakraborty & Mondal (2017) used osmotic dehydration as a pretreatment to vacuum infrared drying of rectangular slabs. Immersing rinds in sucrose solution for 14 h at 50 °C is the preferred condition for candies with the most acceptable characteristics (Hani et al., 2014).…”
Section: Pre‐processed Fruits and Their Process Conditionsmentioning
confidence: 99%
“…Liu et al (2022) studied the effect of far-infrared radiation technology on the quality characteristics of blueberry, and the results showed that the samples had higher thermal stability, apparent quality, and more regular microporous structure after intermittent vacuum far-infrared radiation drying. At present, vacuum far-infrared drying technology has been initially applied in the dehydration of agricultural products such as lotus seeds, cistanche slices (Jiang et al, 2022), watermelon (Rajat & Pijus, 2017), and so forth. However, single vacuum far-infrared drying has an unsatisfactory effect on enhancing mass transfer, although it has a significant positive effect on improving heat transfer during the drying process.…”
Section: Introductionmentioning
confidence: 99%